MARS/NDRI/KSU Communications Workshop: Part 1. Introductory Material - Leslie, John F.; Harvey, Jagger J.W.; Morris, Jeffery B.; Zhang, Guangtao; Gurung, Jaya (My University, 2022)
A. Agenda – Pages 1-2 B. List of attendees – Pages 3-4 C. Group photo of participants – Page 5
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication